Aspects of Science Ethics - Tsakova, Violeta (Research Papers, 2009)
In those studios a big range of problems concerning science ethics in its manifestation forms are being analyzed and offered for discussion. The ethics aspects of number of behaviors, which arise between scientists in science communication process, in discussion, in estimation and publishing of science researches results are being considered.Special attention is given to the essence and faults in estimation and scientist progress mechanism, forms of intellectual exploitation in science and to plagiarism.Ideas and suggestions for solving most of the problems discussed are given.